The moderating role of mindfulness in the relationship between threat appraisal and negative emotions in male elite footballers - Serdar Solmaz; Yunus Emre Yarayan (Journal of Men's Health, 2025)
Background: The aim of this study is to examine the relationship between perceived threat appraisal before competition and negative emotions in elite football players, and to analyze the moderating role of mindfulness in this relationship. Methods: A cross-sectional study was conducted with 299 elite male football players from Turkish football leagues. Data were collected using the Mindfulness Inventory for Sport, Emotions Inventory for Sport, and Challenge and Threat Scale. The data were analyzed using Structural Equation Modeling (SEM). Results: The results revealed a positive correlation between threat appraisal and negative emotions, indicating that higher threat appraisal is associated with increased negative emotions. Mindfulness was found to have a negative relationship with both threat appraisal and negative emotions. Additionally, mindfulness was found to mitigate the relationship between threat appraisal and negative emotions, suggesting that mindfulness can help manage the emotional impact of threat appraisal. Conclusions: These findings imply that athletes’ emotional states can be better regulated in high-pressure situations through mindfulness. The study provides practical implications for athletes and coaches, and emphasizes the need for further longitudinal and experimental research to explore the effects of threat appraisal and mindfulness in greater detail.